An Ass in a Lion's Skin. Issue 2 (3rd March 2021) - Doane, Sébastien
Abstract : The book of Genesis gives two opposing portraits of Judah's masculinity. On the one hand, he is shown as the leader of Jacob's sons, and on the other he is ridiculed by his daughter-in-law. Is Judah an ass in a lion's skin? This article explores Judah's antithetical masculinities as examples of the inherently unstable nature of gender construction. Although Judah is only the fourth son of Jacob, he is expressly depicted in Genesis as assuming a leadership role in relation to his brothers, including speaking up against killing Joseph, negotiating with his father regarding Joseph's demand that Benjamin be brought down to Egypt, and pleading with Joseph for Benjamin's life. In Genesis 49: 8–12, Judah receives the most favourable treatment of all Jacob's sons. The blessing of Jacob from his deathbed portrays Judah's hegemonic masculinity at its finest. However, in Genesis 38, Judah's masculine performance far from ideal biblical masculinity. Not only does Judah lack persuasiveness when he accuses Tamar, but she is able to persuade him that his own actions were wrong. Judah is deceived, specifically deceived by a woman. The shame he wants to attribute to Tamar rebounds on himself. In the end, he acknowledges himself to be less righteous than Tamar (Gen 38: 26). The episode as a whole reveals that Judah does not have control of his family. Genesis 38 clearly subverts Judah's hegemonic masculinity. What are the rhetorical effects of this subversion of Judah's hegemonic gender construction? Jacob speaks of Judah as a lion, but in Genesis 38 he seems to have been portrayed in the role of the ass.